No difference found in time to publication by statistical significance of trial results: a methodological review. (September 2016) - Jefferson, L; Fairhurst, C; Cooper, E; Hewitt, C; Torgerson, T; Cook, L; Tharmanathan, P; Cockayne, S; Torgerson, D
Objective: Time-lag from study completion to publication is a potential source of publication bias in randomised controlled trials. This study sought to update the evidence base by identifying the effect of the statistical significance of research findings on time to publication of trial results. Design: Literature searches were carried out in four general medical journals from June 2013 to June 2014 inclusive ( BMJ, JAMA, the Lancet and the New England Journal of Medicine ). Setting: Methodological review of four general medical journals. Participants: Original research articles presenting the primary analyses from phase 2, 3 and 4 parallel-group randomised controlled trials were included. Main outcome measures: Time from trial completion to publication. Results: The median time from trial completion to publication was 431 days ( n = 208, interquartile range 278–618). A multivariable adjusted Cox model found no statistically significant difference in time to publication for trials reporting positive or negative results (hazard ratio: 0.86, 95% CI 0.64 to 1.16, p = 0.32). Conclusion: In contrast to previous studies, this review did not demonstrate the presence of time-lag bias in time to publication. This may be a result of these articles being published in four high-impact general medical journals that may be more inclined to publish rapidly, whatever the findings. Further research is needed to explore the presence of time-lag bias in lower quality studies and lower impact journals.